A work and systems and procedures study on the Bank of the Philippine Islands (Loyola Branch) - Buan, Melanie C.; Maramba, Amyzola N.; Triunfante, Anna Marie R. (Diliman, Quezon City College of Engineering, 1998)
Considered as one of the premiere banks in the Philippines, the Bank of the Philippine Islands has been the pioneer of various banking services in the country. The group conducted a work and systems and procedures study in the bank. The study aims to increase the efficiency of the present system and improve on the present methods and services. The present system has been documented by the group and was analyzed using stream analysis, work sampling and time study. Through the analysis made, the group came up with the following alternatives : (1) creation of new express lanes; (2) improved queueing system and lobby layout; (3) improved teller cage layout : (4) equal work distribution; and (5) 100 percent manning of all teller cages. Among these five alternatives the group came up with two recommendations : creation of express lanes and improved queueing system and lobby layout. The effects of these recommendations will increase the efficiency of the system and improve the present methods and services.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis